2020
DOI: 10.1111/apt.15781
|View full text |Cite
|
Sign up to set email alerts
|

Reducing variation in hospital mortality for alcohol‐related liver disease in North West England

Abstract: Summary Background Variations in emergency care quality for alcohol‐related liver disease (ARLD) have been highlighted. Aim To determine whether introduction of a regional quality improvement (QI) programme was associated with a reduction in potentially avoidable inpatient mortality. Method Retrospective observational cohort study using hospital administrative data spanning a 1‐year period before (2014/2015) and 3 years after a QI initiative at seven acute hospitals in North West England. The intervention incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Full methods of the algorithm have been published elsewhere. 7 In brief, ICD‐10 codes must conform to one of four patterns (Table 1 and Table S4 ): (1) ArLD‐specific codes as a primary diagnosis (standard approach); (2) ArLD‐specific code as a secondary diagnosis with all higher order diagnoses either a symptom, sign or complication of liver disease or another alcohol‐specific diagnosis; (3) nonspecific liver disease recorded as a primary diagnosis with all lower order diagnoses either a symptom, sign or complication of liver disease or an alcohol‐specific diagnosis; (4) nonspecific liver disease recorded as a secondary diagnosis with all higher order diagnoses either a symptom, sign or complication of liver disease or alcohol‐specific diagnosis. Each care episode contains up to 23 diagnostic codes assigned by clinical coders after discharge using the International Classification of Disease 10th Revision.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Full methods of the algorithm have been published elsewhere. 7 In brief, ICD‐10 codes must conform to one of four patterns (Table 1 and Table S4 ): (1) ArLD‐specific codes as a primary diagnosis (standard approach); (2) ArLD‐specific code as a secondary diagnosis with all higher order diagnoses either a symptom, sign or complication of liver disease or another alcohol‐specific diagnosis; (3) nonspecific liver disease recorded as a primary diagnosis with all lower order diagnoses either a symptom, sign or complication of liver disease or an alcohol‐specific diagnosis; (4) nonspecific liver disease recorded as a secondary diagnosis with all higher order diagnoses either a symptom, sign or complication of liver disease or alcohol‐specific diagnosis. Each care episode contains up to 23 diagnostic codes assigned by clinical coders after discharge using the International Classification of Disease 10th Revision.…”
Section: Methodsmentioning
confidence: 99%
“…The algorithm was quality assured by two independent analysts by comparison to previously published admission data from seven acute NHS hospitals in the North West of England. 7 The LAA was applied to HES data between the financial years 2014/15 to 2017/18…”
Section: Quality Assurance Of the Application Of The Laa To Hesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regionally, standardised care bundles, as advocated for in previous Lancet Commission Reviews, have been shown to reduce variation between hospitals in mortality rates for patients admitted with alcohol-related liver disease. 34 Medical directors should work alongside specialist commissioners to identify appropriate locations. Public Health England's Atlas of Variation in liver outcomes provides a framework to identify areas with the highest need.…”
Section: Masterplan For Improving Survival In Acute Hospitalsmentioning
confidence: 99%
“…It also includes ‘secondary diagnoses’, or in other words, diagnoses that were coded but not in the first data field of a record of an admission episode. In addition it includes a wider set of ICD‐10 codes that encompass complications of ALD, non‐specific liver disease and other alcohol‐specific diseases 6 …”
mentioning
confidence: 99%